A high thermal conductivity mold copper for automobile component production mold and its manufacturing process

By using copper/diamond composite materials, combined with heat diffusion method and multiple heat treatment processes, the problem of failure of existing mold materials at high temperatures is solved, high thermal conductivity and high thermal stability are achieved, and new performance requirements for mold production of automobile components are met.

CN119753467APending Publication Date: 2025-04-04DONGGUAN WEIHAO MOLDING TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510084190.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing automotive component production mold materials fail at high temperatures and cannot meet the new requirements for material performance during hot pressing or hot extrusion molding.

Method used

Copper/diamond composite material is used as the high-thermal conductivity mold material, diamond is modified through the heat diffusion method and composited with the copper matrix, combined with multiple heat treatment processes to improve the thermal conductivity and high temperature stability of the material.

Benefits of technology

It achieves high thermal conductivity and high thermal stability, meeting the needs of automotive component production molds at high temperatures.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a high thermal conductivity mold copper for automobile component production molds and a manufacturing process thereof, and belongs to the technical field of metal materials. The manufacturing process of the high thermal conductivity mold copper disclosed in the present invention specifically includes the following steps: (1) using copper as a matrix and compounding it with pre-treated modified diamond to obtain a copper / diamond composite material; (2) the copper / diamond composite material is first subjected to high-temperature diffusion heat treatment, then forged hot processing, and forged cooling; (3) then annealed heat treatment, hydrogen expansion and tempering treatment; (4) finally quenched and tempered to complete the entire process. Diamond is modified with tungsten powder by a thermal diffusion method, and is compounded with a copper matrix by an oscillating hot pressing process. The obtained copper / diamond composite material has good uniformity and gives it high thermal conductivity. At the same time, multiple heat treatments are performed to improve the high thermal stability of the mold.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal materials and relates to a high thermal conductivity mold copper for automobile component production molds and a manufacturing process thereof. Background Art

[0002] In order to save energy, countries around the world have increased the operating temperature of machines that convert heat into electrical energy or heat into kinetic energy to improve their efficiency. As a result, the materials of some of the matching parts have become ineffective due to heat resistance. In addition, with the adoption of new processes for hot pressing or hot extrusion molding of plastic, non-ferrous metal or steel parts, the molding temperature and pressure have increased, and the materials originally used to manufacture molds can no longer meet the new performance requirements.

[0003] Diamond is an atomic crystal composed of carbon atoms. In its crystal structure, each carbon atom forms a covalent α bond with the surrounding four carbon atoms in the form of sp3 hybridization. Since the formed CC covalent bond has a high bond strength, it has a high hardness and melting point. All carbon atoms in diamond participate in bonding, and there are no free electrons. Therefore, the thermal conductivity of diamond does not rely on the directional movement of free electrons, but on lattice vibration. This lattice vibration is called phonon. Due to the small mass of carbon elements and the large bond strength of CC bonds, phonons can propagate quickly in diamond crystals, which manifests as extremely high thermal conductivity on a macro scale. The thermal conductivity of natural diamond can reach 2000W / m˙K, which is the material with the highest thermal conductivity in nature.

[0004] The diamond / copper interface structure is an important factor affecting the thermal conductivity of its composite materials. The wettability between diamond particles and metal matrix, whether the interface reaction occurs at the interface, and other issues will have a huge impact on the thermal conductivity of diamond / copper composite materials. Since the coordination number of carbon atoms on the diamond surface is less than 4, the outermost electrons are not fully bonded, and there are dangling bonds on the surface carbon atoms. The dangling bonds are bonded by self-coupling closure or adsorption of gas atoms to form a stable diamond surface, resulting in diamond with low surface energy and difficult to be wetted by most metals. According to the valence bond theory, when the transition metal d orbital is vacant, the outermost electrons of the carbon atom can enter the d orbital to form carbides. The 3d orbital of the copper atom is in a fully filled state, so it cannot react with the carbon atom to form carbides. Therefore, the diamond particles can neither be wetted by copper nor form carbides with copper. How to improve the interface bonding between diamond particles and the copper matrix has become the most important issue in the study of diamond / copper composite materials. Summary of the invention

[0005] The present invention relates to a high thermal conductivity mold copper for automobile component production molds and a manufacturing process thereof, and belongs to the technical field of metal materials. The manufacturing process of the high thermal conductivity mold copper disclosed in the present invention specifically includes the following steps: (1) using copper as a matrix and compounding it with pre-treated modified diamond to obtain a copper / diamond composite material; (2) the copper / diamond composite material is first subjected to high-temperature diffusion heat treatment, then forged hot processing, and forged cooling; (3) then annealed heat treatment, hydrogen expansion and tempering treatment; (4) finally quenched and tempered to complete the entire process. Diamond is modified with tungsten powder by a thermal diffusion method, and is compounded with a copper matrix by an oscillating hot pressing process. The obtained copper / diamond composite material has good uniformity and gives it high thermal conductivity. At the same time, multiple heat treatments are performed to improve the high thermal stability of the mold.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A high thermal conductivity mold copper for automobile component production molds, the raw materials of which include: copper sulfate, tungsten powder, and diamond particles, wherein the particle size of the diamond is less than 100 nanometers.

[0007] A manufacturing process of high thermal conductivity mold copper for automobile component production molds, the manufacturing process of high thermal conductivity mold copper for automobile component production molds specifically comprises the following steps: (1) Pretreatment of diamond: diamond particles are placed in a sodium hydroxide solution, heated and stirred, then filtered, the solid is washed with water, placed in a drying oven to dry to obtain particles, then mixed with a hydrochloric acid solution, heated and stirred, then filtered, the solid is washed with water, and dried to obtain pretreated diamond; (2) Pre-treated diamond is mixed with tungsten powder, ground using a drum ball mill, and then heated and kept warm in a vacuum, and then cooled to room temperature to obtain modified diamond; (3) First, the modified diamond is placed in tin chloride and stirred, then filtered, washed with water and dried to obtain the pre-treated modified diamond; (4) copper sulfate, pretreated modified diamond, formaldehyde, a complexing agent and a stabilizer are mixed, heated, sodium hydroxide solution is added to adjust the pH value, and then filtered, and the solid is washed and dried to obtain a copper / diamond composite material; (5) The copper / diamond composite material is heated in a multi-stage heating method, at 500°C, 800°C and 1000°C respectively, and finally heated to 1100°C and kept at this temperature for 10-12h; (6) then heated to 1200-1250°C for forging, and then cooled to 160-180°C; (7) Then it is placed in an annealing heating furnace for annealing treatment, followed by hydrogen expansion annealing treatment, and finally quenching and tempering heat treatment, thus completing the entire process.

[0008] Furthermore, in the step (1), the solid-liquid ratio of the diamond particles to the sodium hydroxide solution is 1-2 g: 10-15 mL, wherein the mass fraction of the sodium hydroxide solution is 8-10%, the heating temperature is 80-90° C., the stirring time is 90-120 min, the solid-liquid ratio of the particles to the hydrochloric acid solution is 1-3 g: 5-7 mL, wherein the mass fraction of the hydrochloric acid solution is 18-20%, and the heating and stirring temperature and time are 60-70° C. and 90-120 min, respectively.

[0009] Furthermore, in the step (2), the mass ratio of the pretreated diamond to the tungsten powder is 1-3:1, the grinding speed and time are 80-100 rpm and 3-5 h respectively, and the heating and insulation temperature and time are 1000-1100° C. and 3-5 h respectively.

[0010] Furthermore, in the step (3), the solid-liquid ratio of the modified diamond to tin chloride is 2-4 g:1-3 mL, and the stirring time is 40-60 min.

[0011] Furthermore, in the step (4), the mass ratio of copper sulfate, pretreated modified diamond, formaldehyde, complexing agent and stabilizer is 1:1-2:0.5:0.2-0.4:0.3, wherein the complex is composed of EDTA and sodium tartrate in a mass ratio of 1:1, the concentration of sodium tartrate is 12-14 g / L, the concentration of copper sulfate is 15-17 g / L, the stabilizer is potassium ferrocyanide, and its concentration is 0.02-0.04 g / L, the heating temperature and time are 50-60°C and 2-3h respectively, the mass fraction of the sodium hydroxide solution is 10-12%, and the pH value is 10-12.

[0012] Furthermore, the temperature and time of the annealing treatment in step (7) are 800-900° C. and 5-7 h, respectively, and the temperature and time of the hydrogen expansion annealing treatment are 500-600° C. and 10-12 h, respectively.

[0013] Furthermore, the quenching and tempering treatment is: heating to 850-900°C, then cooling to 200°C, followed by tempering at 500-550°C, and tempering and heat preservation for 2-4h.

[0014] Beneficial effects of the present invention: The present invention uses tungsten powder to modify diamond by thermal diffusion method, and composites it with copper matrix by oscillating hot pressing process. The obtained copper / diamond composite material has good uniformity and endows it with high thermal conductivity. At the same time, multiple heat treatments are performed to improve the high thermal stability of the mold. DETAILED DESCRIPTION

[0015] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0016] The particle size of the tungsten powder involved in the present invention is 50nm.

[0017] Example 1 A high thermal conductivity mold copper for automobile component production molds, the raw materials of which include: copper sulfate, tungsten powder, and diamond particles, wherein the particle size of the diamond is less than 100 nanometers.

[0018] A manufacturing process of high thermal conductivity mold copper for automobile component production molds, the manufacturing process of high thermal conductivity mold copper for automobile component production molds specifically comprises the following steps: (1) Pretreatment of diamond: diamond particles are placed in a sodium hydroxide solution, heated and stirred, then filtered, the solid is washed with water, placed in a drying oven to dry to obtain particles, then mixed with a hydrochloric acid solution, heated and stirred, then filtered, the solid is washed with water, and dried to obtain pretreated diamond; (2) Pre-treated diamond is mixed with tungsten powder, ground using a drum ball mill, and then heated and kept warm in a vacuum, and then cooled to room temperature to obtain modified diamond; (3) First, the modified diamond is placed in tin chloride and stirred, then filtered, washed with water and dried to obtain the pre-treated modified diamond; (4) copper sulfate, pretreated modified diamond, formaldehyde, a complexing agent and a stabilizer are mixed, heated, sodium hydroxide solution is added to adjust the pH value, and then filtered, and the solid is washed and dried to obtain a copper / diamond composite material; (5) The copper / diamond composite material was heated in a multi-stage heating method, heated in a temperature range of 500°C, and finally heated to 1100°C and kept at this temperature for 10 h; (6) then heated to 1200°C for forging, and then cooled to 160°C; (7) Then it is placed in an annealing heating furnace for annealing treatment, followed by hydrogen expansion annealing treatment, and finally quenching and tempering heat treatment, thus completing the entire process.

[0019] In the step (1), the solid-liquid ratio of the diamond particles to the sodium hydroxide solution is 1 g:10 mL, wherein the mass fraction of the sodium hydroxide solution is 8%, the heating temperature is 80° C., and the stirring time is 90 min. The solid-liquid ratio of the particles to the hydrochloric acid solution is 1 g:5 mL, wherein the mass fraction of the hydrochloric acid solution is 18%, and the temperature and time of the heating and stirring are 60° C. and 90 min, respectively.

[0020] In the step (2), the mass ratio of pretreated diamond to tungsten powder is 1:1, the grinding speed and time are 80 rpm and 3 h respectively, and the heating and insulation temperature and time are 1000° C. and 3 h respectively.

[0021] In the step (3), the solid-to-liquid ratio of modified diamond to tin chloride is 2 g:1 mL, and the stirring time is 40 min.

[0022] In the step (4), the mass ratio of copper sulfate, pretreated modified diamond, formaldehyde, complexing agent and stabilizer is 1:1:0.5:0.2:0.3, wherein the complex is composed of EDTA and sodium tartrate in a mass ratio of 1:1, the concentration of sodium tartrate is 12 g / L, the concentration of copper sulfate is 15 g / L, the stabilizer is potassium ferrocyanide, and its concentration is 0.02 g / L, the heating temperature and time are 50°C and 2 h respectively, the mass fraction of the sodium hydroxide solution is 10%, and the pH value is 10.

[0023] The temperature and time of the annealing treatment in step (7) are 800° C. and 5 h respectively, and the temperature and time of the hydrogen expansion annealing treatment are 500° C. and 10 h respectively.

[0024] The quenching and tempering treatment is as follows: heating to 850°C, then cooling to 200°C, followed by tempering at 500°C, and tempering and heat preservation for 2h.

[0025] Example 2 A high thermal conductivity mold copper for automobile component production molds, the raw materials of which include: copper sulfate, tungsten powder, and diamond particles, wherein the particle size of the diamond is less than 100 nanometers.

[0026] A manufacturing process of high thermal conductivity mold copper for automobile component production molds, the manufacturing process of high thermal conductivity mold copper for automobile component production molds specifically comprises the following steps: (1) Pretreatment of diamond: diamond particles are placed in a sodium hydroxide solution, heated and stirred, then filtered, the solid is washed with water, placed in a drying oven to dry to obtain particles, then mixed with a hydrochloric acid solution, heated and stirred, then filtered, the solid is washed with water, and dried to obtain pretreated diamond; (2) Pre-treated diamond is mixed with tungsten powder, ground using a drum ball mill, and then heated and kept warm in a vacuum, and then cooled to room temperature to obtain modified diamond; (3) First, the modified diamond is placed in tin chloride and stirred, then filtered, washed with water and dried to obtain the pre-treated modified diamond; (4) copper sulfate, pretreated modified diamond, formaldehyde, a complexing agent and a stabilizer are mixed, heated, sodium hydroxide solution is added to adjust the pH value, and then filtered, and the solid is washed and dried to obtain a copper / diamond composite material; (5) The copper / diamond composite material was heated in a multi-stage heating method, heated in a temperature range of 800°C, and finally heated to 1100°C and kept at this temperature for 11 hours; (6) then heated to 1200°C for forging, and then cooled to 170°C; (7) Then it is placed in an annealing heating furnace for annealing treatment, followed by hydrogen expansion annealing treatment, and finally quenching and tempering heat treatment, thus completing the entire process.

[0027] In the step (1), the solid-liquid ratio of the diamond particles to the sodium hydroxide solution is 1.5 g:13 mL, wherein the mass fraction of the sodium hydroxide solution is 9%, the heating temperature is 85° C., and the stirring time is 105 min. The solid-liquid ratio of the particles to the hydrochloric acid solution is 2 g:6 mL, wherein the mass fraction of the hydrochloric acid solution is 19%, and the temperature and time of the heating and stirring are 65° C. and 105 min, respectively.

[0028] In the step (2), the mass ratio of pretreated diamond to tungsten powder is 1.5:1, the grinding speed and time are 90 rpm and 4 h respectively, and the heating and insulation temperature and time are 1050° C. and 4 h respectively.

[0029] In the step (3), the solid-to-liquid ratio of modified diamond to tin chloride is 3 g:2 mL, and the stirring time is 50 min.

[0030] In the step (4), the mass ratio of copper sulfate, pretreated modified diamond, formaldehyde, complexing agent and stabilizer is 1:1.5:0.5:0.3:0.3, wherein the complex is composed of EDTA and sodium tartrate in a mass ratio of 1:1, the concentration of sodium tartrate is 13 g / L, the concentration of copper sulfate is 16 g / L, the stabilizer is potassium ferrocyanide, and its concentration is 0.03 g / L, the heating temperature and time are 55°C and 2.5 h respectively, the mass fraction of the sodium hydroxide solution is 11%, and the pH value is 11.

[0031] The temperature and time of the annealing treatment in step (7) are 850° C. and 6 h respectively, and the temperature and time of the hydrogen expansion annealing treatment are 550° C. and 11 h respectively.

[0032] The quenching and tempering treatment is as follows: heating to 880°C, then cooling to 200°C, followed by tempering at 525°C, and tempering and heat preservation for 3h.

[0033] Example 3 A high thermal conductivity mold copper for automobile component production molds, the raw materials of which include: copper sulfate, tungsten powder, and diamond particles, wherein the particle size of the diamond is less than 100 nanometers.

[0034] A manufacturing process of high thermal conductivity mold copper for automobile component production molds, the manufacturing process of high thermal conductivity mold copper for automobile component production molds specifically comprises the following steps: (1) Pretreatment of diamond: diamond particles are placed in a sodium hydroxide solution, heated and stirred, then filtered, the solid is washed with water, placed in a drying oven to dry to obtain particles, then mixed with a hydrochloric acid solution, heated and stirred, then filtered, the solid is washed with water, and dried to obtain pretreated diamond; (2) Pre-treated diamond is mixed with tungsten powder, ground using a drum ball mill, and then heated and kept warm in a vacuum, and then cooled to room temperature to obtain modified diamond; (3) First, the modified diamond is placed in tin chloride and stirred, then filtered, washed with water and dried to obtain the pre-treated modified diamond; (4) copper sulfate, pretreated modified diamond, formaldehyde, a complexing agent and a stabilizer are mixed, heated, sodium hydroxide solution is added to adjust the pH value, and then filtered, and the solid is washed and dried to obtain a copper / diamond composite material; (5) The copper / diamond composite material was heated in a multi-stage heating method, heated in a temperature range of 1000°C, and finally heated to 1100°C and kept at this temperature for 12 h; (6) then heated to 1250°C for forging, and then cooled to 180°C; (7) Then it is placed in an annealing heating furnace for annealing treatment, followed by hydrogen expansion annealing treatment, and finally quenching and tempering heat treatment, thus completing the entire process.

[0035] In the step (1), the solid-liquid ratio of the diamond particles to the sodium hydroxide solution is 2g:15mL, wherein the mass fraction of the sodium hydroxide solution is 10%, the heating temperature is 90°C, and the stirring time is 120min. The solid-liquid ratio of the particles to the hydrochloric acid solution is 3g:7mL, wherein the mass fraction of the hydrochloric acid solution is 20%, and the temperature and time of the heating and stirring are 70°C and 120min, respectively.

[0036] In the step (2), the mass ratio of pretreated diamond to tungsten powder is 3:1, the grinding speed and time are 100 rpm and 5 h respectively, and the heating and insulation temperature and time are 1100° C. and 5 h respectively.

[0037] In the step (3), the solid-to-liquid ratio of modified diamond to tin chloride is 4 g:3 mL, and the stirring time is 60 min.

[0038] In the step (4), the mass ratio of copper sulfate, pretreated modified diamond, formaldehyde, complexing agent and stabilizer is 1:2:0.5:0.4:0.3, wherein the complex is composed of EDTA and sodium tartrate in a mass ratio of 1:1, the concentration of sodium tartrate is 14 g / L, the concentration of copper sulfate is 17 g / L, the stabilizer is potassium ferrocyanide, and its concentration is 0.04 g / L, the heating temperature and time are 60°C and 3 h respectively, the mass fraction of the sodium hydroxide solution is 12%, and the pH value is 12.

[0039] The temperature and time of the annealing treatment in step (7) are 900° C. and 7 h respectively, and the temperature and time of the hydrogen expansion annealing treatment are 600° C. and 12 h respectively.

[0040] The quenching and tempering treatment is as follows: heating to 900°C, then cooling to 200°C, followed by tempering at 550°C, and tempering and heat preservation for 4h.

[0041] Comparative Example 1 The difference from Example 2 is that the diamond does not undergo a pretreatment step, and other conditions are consistent with Example 2.

[0042] Comparative Example 2 The difference from Example 2 is that the pretreated diamond does not undergo the tungsten powder modification step, and other conditions are consistent with Example 2.

[0043] Comparative Example 3 The difference from Example 2 is that the modified diamond does not undergo a pretreatment step, and other conditions are consistent with Example 2.

[0044] Comparative Example 4 On the basis of Example 2, a high thermal conductivity mold copper for automobile component production mold is provided. The raw materials of the high thermal conductivity mold copper for automobile component production mold include: copper sulfate, tungsten powder, and diamond particles. The particle size of the diamond is less than 100 nanometers.

[0045] A manufacturing process of high thermal conductivity mold copper for automobile component production molds, the manufacturing process of high thermal conductivity mold copper for automobile component production molds specifically comprises the following steps: (1) Pretreatment of diamond: diamond particles are placed in a sodium hydroxide solution, heated and stirred, and then filtered. The solid is washed with water and placed in a drying oven for drying to obtain pretreated diamond; (2) Pre-treated diamond is mixed with tungsten powder, ground using a drum ball mill, and then heated and kept warm in a vacuum, and then cooled to room temperature to obtain modified diamond; (3) First, the modified diamond is placed in tin chloride and stirred, then filtered, washed with water and dried to obtain the pre-treated modified diamond; (4) copper sulfate, pretreated modified diamond, formaldehyde, a complexing agent and a stabilizer are mixed, heated, sodium hydroxide solution is added to adjust the pH value, and then filtered, and the solid is washed and dried to obtain a copper / diamond composite material; (5) The copper / diamond composite material was heated in a multi-stage heating method, heated in a temperature range of 800°C, and finally heated to 1100°C and kept at this temperature for 11 hours; (6) then heated to 1200°C for forging, and then cooled to 170°C; (7) Then it is placed in an annealing heating furnace for annealing treatment, followed by hydrogen expansion annealing treatment, and finally quenching and tempering heat treatment, thus completing the entire process.

[0046] In the step (1), the solid-to-liquid ratio of diamond particles to sodium hydroxide solution is 1.5 g:13 mL, wherein the mass fraction of the sodium hydroxide solution is 9%, the heating temperature is 85° C., and the stirring time is 105 min.

[0047] In the step (2), the mass ratio of pretreated diamond to tungsten powder is 1.5:1, the grinding speed and time are 90 rpm and 4 h respectively, and the heating and insulation temperature and time are 1050° C. and 4 h respectively.

[0048] In the step (3), the solid-to-liquid ratio of modified diamond to tin chloride is 3 g:2 mL, and the stirring time is 50 min.

[0049] In the step (4), the mass ratio of copper sulfate, pretreated modified diamond, formaldehyde, complexing agent and stabilizer is 1:1.5:0.5:0.3:0.3, wherein the complex is composed of EDTA and sodium tartrate in a mass ratio of 1:1, the concentration of sodium tartrate is 13 g / L, the concentration of copper sulfate is 16 g / L, the stabilizer is potassium ferrocyanide, and its concentration is 0.03 g / L, the heating temperature and time are 55°C and 2.5 h respectively, the mass fraction of the sodium hydroxide solution is 11%, and the pH value is 11.

[0050] The temperature and time of the annealing treatment in step (7) are 850° C. and 6 h respectively, and the temperature and time of the hydrogen expansion annealing treatment are 550° C. and 11 h respectively.

[0051] The quenching and tempering treatment is as follows: heating to 880°C, then cooling to 200°C, followed by tempering at 525°C, and tempering and heat preservation for 3h.

[0052] Comparative Example 5 On the basis of Example 2, a high thermal conductivity mold copper for automobile component production mold is provided. The raw materials of the high thermal conductivity mold copper for automobile component production mold include: copper sulfate, tungsten powder, and diamond particles. The particle size of the diamond is less than 100 nanometers.

[0053] A manufacturing process of high thermal conductivity mold copper for automobile component production molds, the manufacturing process of high thermal conductivity mold copper for automobile component production molds specifically comprises the following steps: (1) Pre-treatment of diamond: diamond particles are mixed in hydrochloric acid solution, heated and stirred, then filtered, the solid is washed with water, and dried to obtain pre-treated diamond; (2) Pre-treated diamond is mixed with tungsten powder, ground using a drum ball mill, and then heated and kept warm in a vacuum, and then cooled to room temperature to obtain modified diamond; (3) First, the modified diamond is placed in tin chloride and stirred, then filtered, washed with water and dried to obtain the pre-treated modified diamond; (4) copper sulfate, pretreated modified diamond, formaldehyde, a complexing agent and a stabilizer are mixed, heated, sodium hydroxide solution is added to adjust the pH value, and then filtered, and the solid is washed and dried to obtain a copper / diamond composite material; (5) The copper / diamond composite material was heated in a multi-stage heating method, heated in a temperature range of 800°C, and finally heated to 1100°C and kept at this temperature for 11 hours; (6) then heated to 1200°C for forging, and then cooled to 170°C; (7) Then it is placed in an annealing heating furnace for annealing treatment, followed by hydrogen expansion annealing treatment, and finally quenching and tempering heat treatment, thus completing the entire process.

[0054] In the step (1), the solid-liquid ratio of diamond particles to hydrochloric acid solution is 2 g:6 mL, wherein the mass fraction of the hydrochloric acid solution is 19%, and the temperature and time of heating and stirring are 65° C. and 105 min, respectively.

[0055] In the step (2), the mass ratio of pretreated diamond to tungsten powder is 1.5:1, the grinding speed and time are 90 rpm and 4 h respectively, and the heating and insulation temperature and time are 1050° C. and 4 h respectively.

[0056] In the step (3), the solid-to-liquid ratio of modified diamond to tin chloride is 3 g:2 mL, and the stirring time is 50 min.

[0057] In the step (4), the mass ratio of copper sulfate, pretreated modified diamond, formaldehyde, complexing agent and stabilizer is 1:1.5:0.5:0.3:0.3, wherein the complex is composed of EDTA and sodium tartrate in a mass ratio of 1:1, the concentration of sodium tartrate is 13 g / L, the concentration of copper sulfate is 16 g / L, the stabilizer is potassium ferrocyanide, and its concentration is 0.03 g / L, the heating temperature and time are 55°C and 2.5 h respectively, the mass fraction of the sodium hydroxide solution is 11%, and the pH value is 11.

[0058] The temperature and time of the annealing treatment in step (7) are 850° C. and 6 h respectively, and the temperature and time of the hydrogen expansion annealing treatment are 550° C. and 11 h respectively.

[0059] The quenching and tempering treatment is as follows: heating to 880°C, then cooling to 200°C, followed by tempering at 525°C, and tempering and heat preservation for 3h.

[0060] Performance Testing The mold copper prepared in Examples 1-3 and Comparative Examples 1-5 was used as a sample, and the thermal diffusion coefficient was tested by laser flash method. The sample was tested by laser thermal conductivity instrument. The sample size was φ12.7 mm and the thickness was 3 mm. The sample was carbon sprayed before the test to reduce the reflection of the heat signal and ensure the uniform surface temperature of the sample. The thermal conductivity of the material can be calculated by the following formula: Wherein, a is the thermal diffusion coefficient of the composite material, ρ is the volume density of the composite material, and C is the specific heat capacity of the composite material. The test results are shown in Table 1.

[0061] Table 1 Test results Sample Thermal conductivity W / m˙K Example 1 1156 Example 2 1160 Example 3 1150 Comparative Example 1 890 Comparative Example 2 720 Comparative Example 3 903 Comparative Example 4 960 Comparative Example 5 980 From the data analysis of Table 1, it can be seen that the thermal conductivity of Examples 1-3 is much greater than that of Comparative Examples 1-5, among which Comparative Example 2 has the lowest thermal conductivity. Comparative Example 1 has not been subjected to degreasing and surface roughening treatment, which affects the bonding between the diamond particles and the tungsten powder; the diamond particles in Comparative Example 2 have not been modified by the tungsten powder, which affects the interface between the diamond particles and the copper matrix; the modified diamond particles in Comparative Example 3 have not been activated, which affects the composite interface with the copper matrix; Comparative Examples 4-5 have not been subjected to degreasing or surface roughening treatment, which reduces the bonding with the tungsten powder, so the thermal conductivity of Comparative Examples 1-5 is lower than that of Examples 1-3.

[0062] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A high thermal conductivity mold copper for automobile component production mold, characterized in that: The raw materials of the high thermal conductivity mold copper for automobile component production mold include: copper sulfate, tungsten powder, and diamond particles, and the particle size of the diamond is less than 100 nanometers.

2. A manufacturing process for high thermal conductivity mold copper for automobile component production molds as claimed in claim 1, characterized in that: The manufacturing process of high thermal conductivity mold copper for automobile component production molds is specifically as follows: (1) Pretreatment of diamond: diamond particles are placed in a sodium hydroxide solution, heated and stirred, then filtered, the solid is washed with water, placed in a drying oven to dry to obtain particles, then mixed with a hydrochloric acid solution, heated and stirred, then filtered, the solid is washed with water, and dried to obtain pretreated diamond; (2) Pre-treated diamond is mixed with tungsten powder, ground using a drum ball mill, and then heated and kept warm in a vacuum, and then cooled to room temperature to obtain modified diamond; (3) First, the modified diamond is placed in tin chloride and stirred, then filtered, washed with water and dried to obtain the pre-treated modified diamond; (4) copper sulfate, pretreated modified diamond, formaldehyde, a complexing agent and a stabilizer are mixed, heated, sodium hydroxide solution is added to adjust the pH value, and then filtered, and the solid is washed and dried to obtain a copper / diamond composite material; (5) The copper / diamond composite material is heated in a multi-stage heating method, at 500°C, 800°C and 1000°C respectively, and finally heated to 1100°C and kept at this temperature for 10-12h; (6) then heated to 1200-1250°C for forging, and then cooled to 160-180°C; (7) Then it is placed in an annealing heating furnace for annealing treatment, followed by hydrogen expansion annealing treatment, and finally quenching and tempering heat treatment, thus completing the entire process.

3. The manufacturing process of a high thermal conductivity mold copper for automobile component production mold according to claim 2, characterized in that: In the step (1), the solid-liquid ratio of the diamond particles to the sodium hydroxide solution is 1-2 g: 10-15 mL, wherein the mass fraction of the sodium hydroxide solution is 8-10%, the heating temperature is 80-90° C., and the stirring time is 90-120 min. The solid-liquid ratio of the particles to the hydrochloric acid solution is 1-3 g: 5-7 mL, wherein the mass fraction of the hydrochloric acid solution is 18-20%, and the temperature and time of the heating and stirring are 60-70° C. and 90-120 min, respectively.

4. The manufacturing process of a high thermal conductivity mold copper for automobile component production mold according to claim 2, characterized in that: In the step (2), the mass ratio of the pretreated diamond to the tungsten powder is 1-3:1, the grinding speed and time are 80-100 rpm and 3-5 h respectively, and the heating and insulation temperature and time are 1000-1100° C. and 3-5 h respectively.

5. The manufacturing process of a high thermal conductivity mold copper for automobile component production mold according to claim 2, characterized in that: In the step (3), the solid-to-liquid ratio of modified diamond to tin chloride is 2-4 g:1-3 mL, and the stirring time is 40-60 min.

6. The manufacturing process of a high thermal conductivity mold copper for automobile component production mold according to claim 2, characterized in that: In the step (4), the mass ratio of copper sulfate, pretreated modified diamond, formaldehyde, complexing agent and stabilizer is 1:1-2:0.5:0.2-0.4:0.3, wherein the complex is composed of EDTA and sodium tartrate in a mass ratio of 1:1, the concentration of sodium tartrate is 12-14 g / L, the concentration of copper sulfate is 15-17 g / L, the stabilizer is potassium ferrocyanide, and its concentration is 0.02-0.04 g / L, the heating temperature and time are 50-60°C and 2-3h respectively, the mass fraction of the sodium hydroxide solution is 10-12%, and the pH value is 10-12.

7. The manufacturing process of a high thermal conductivity mold copper for automobile component production mold according to claim 2, characterized in that: The temperature and time of the annealing treatment in step (7) are 800-900° C. and 5-7 h, respectively, and the temperature and time of the hydrogen expansion annealing treatment are 500-600° C. and 10-12 h, respectively.

8. The manufacturing process of high thermal conductivity mold copper for automobile component production mold according to claim 2, characterized in that: The quenching and tempering treatment is as follows: heating to 850-900°C, then cooling to 200°C, followed by tempering at 500-550°C, and tempering and heat preservation for 2-4h.